Extraoral Osseous Choristoma in the Head and Neck Region: Case Report and Literature Review. (28th May 2019) - Arens, Philipp; Ullrich, Andrea; Olze, Heidi; Uecker, Florian Cornelius
Abstract : An osseous choristoma is a benign tumor consisting of regular bone tissue in an irregular localization. Choristomas in the head and neck region are rare. Most frequently, they are found in the region of the tongue or oral mucosa. There are also very few reports on osseous choristomas in the submandibular region. We present the case of a woman with a large, caudal osseous choristoma within the lateral cervical triangle. Literature review is given about all of the reported cases in the region of the neck. The pathogenesis is yet unexplained. Our case supports the theory that the development of an osseous choristoma is a reaction to a former trauma. Cervical osseous choristomas are seldom, but they represent an important differential diagnosis when dealing with a cervical tumor.